Group Technology An Integrated Planning and Implementation Concept for Small and Medium Batch Production - Arn, Ernst Alexander (Springer Berlin Heidelberg, 1975)
Group Technology (GT) as a manufacturing concept has gained steady interest within the machine building industry all over the world. Originally it was used more or less only in the so-called parts family manufacturing concept. With growing opportunities for using the computer in the design process, operating planning and layout planning, the potential advantages became more and more obvious. In order to implement GT successfully and with a view to improving the overall economic situation of a production company, it is necessary to consider all aspects of the com plete manufacturing system. Experience has shown, that in the first stage a general basis has to be formed. This is done by a clear and practical definition of three GT manufacturing systems, the devel opment of a set of classification systems for work pieces, working operations and man ufacturing equipment, and in building a data bank from which a data basis for the GT planning process can be evaluated. A second stage of implementation then considers the particular aspects of GT. These are, firstly, a concept for layout and investment planning based on a representative parts spectrum; secondly, for application of the GT-idea in the design process three similar types of parts are to be developed as a logical supplement to the standard and recurring parts practice; thirdly, a three stage process planning and work measurement system can be developed for the so defined spectrum of similar parts